Soviet Energy Technologies Planning, Policy, Research, and Development - Campbell, Robert W. (Indiana University Press, 1980)
Robert W. Campbell's informed study of Soviet technological capabilities and efforts to innovate in the energy field provides a basis for understanding Soviet energy problems and forecasting future Soviet energy problems and forecasting future Soviet choices among energy options. Drawing on a large body of Soviet source material-publications of research and development organizations, engineering sources, technical journals, and economic publications-the author, a leading expert in Soviet energy matters, gives us a clear picture of the development of Soviet technologies both for producing energy and for exploiting new sources of fuel.